An Application to Fixed-Point Results in Tricomplex-Valued Metric Spaces Using Control Functions - Rajagopalan Ramaswamy; Gunaseelan Mani; Arul Joseph Gnanaprakasam; Ola A. Ashour Abdelnaby; Stojan Radenović (Mathematics, 2022)
In the present work, we establish fixed-point results for a pair of mappings satisfying some contractive conditions on rational expressions with coefficients as point-dependent control functions in the setting of tricomplex-valued metric spaces. The proven results are extension and generalisation of some of the literature’s well-known results. We also explore some of the applications to our key results.